Studi kandungan Fitokimia dan aktivitas anti-hipertensi tanaman ciplukan (Physalis angulate L): Artikel Review - Azzahra, Fatimah (Maliki Interdisciplinary Journal, 2026)
Hypertension is a condition of above-normal blood pressure (≥140/90 mmHg) that is often asymptomatic and can cause serious complications. This study aims to examine the phytochemical content and antihypertensive effects of ciplukan (Physalis angulata L.) as an alternative herbal therapy. The method used was a literature study from various sources over the past 5 years. The results showed that ciplukan contains flavonoids, saponins, alkaloids, steroids, polyphenols, and fisalin, which function as antioxidants, ACE inhibitors, and vasodilators. Interventions with decoctions, juices, or extracts (single or combined) were effective in lowering blood pressure in humans and experimental animals. This plant has potential as an adjunct therapy, particularly in areas with limited access to medication, with recommendations for further research on its clinical mechanisms.